Potential Encapsulating Microparticle from Degreased Dry Flour of Guava Seeds (London Journal of Engineering Research, 2024)
Brazil is one of the world's largest producers of guava. The estimated production is approximately 552,393 tons/year. Most guava production is processed to manufacture juices, nectars, pulps, and ice creams. During the processing of guava, about 40% of the waste from the processing of guava consists of seeds, whose disposal causes environmental problems. Within this context, this work aimed to develop encapsulating material from guava seed flour and to study the kinetics, equilibrium, and thermodynamics involved in the microencapsulation process. Initially, the characterization of the guava seeds (carbohydrates, proteins, fibers, and ashes) was carried out, then the seed yield was calculated. After the characterization, the seed yield was calculated, and these were used to prepare dry and defatted flour. This flour was characterized in terms of solubility, hygroscopicity, bed and compacted density, wettability, morphology, zero load point, and thermal analysis. The experimental parameters of the adsorption process were previously optimized. The adsorption capacity was evaluated in a batch system under a controlled temperature of 25 2C. From the results obtained, it is possible to infer that the dry and defatted seed flour presented the potential for the proposed purpose, with a high capacity to incorporate the methylene blue dye (~83%). The experimental results showed that the pseudo-second-order model better described the adsorption kinetics. Finally, thermodynamic results analysis revealed a spontaneous adsorption process (?G= -44.10 kJ mol-1), exothermic (?H = -22.47 kJ mol-1), and with ?S = -73 .62 J mol-1 K-1, which shows small changes in randomness at the solute-adsorbent interface during adsorption.
Keywords: catalysis catalyst cabatier principle boudart principle